Contents and Forewords of the EDUCARE Journal, Issue of February 2018 - EDUCARE, Editor Journal (EDUCARE, 2018)
EDUCARE: International Journal for Educational Studies.Â This journal, with ISSN 1979-7877, was firstly published on August 17, 2008, in the context to commemorate the anniversary of Indonesian Independence Day. Since issues of February 2009 to February 2016, the EDUCARE journal was organized and managed by the Lecturers of FKIP UMP (Faculty of Education and Teacher Training, Muhammadiyah University of Purwokerto) in Central Java; and published by Minda Masagi Press, as a publisher owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia and BRIMAN (Brunei-Indonesia-Malaysia Academic Network) Institute in Bandar Seri Begawan, Brunei Darussalam, since 2018 to date. The EDUCARE journal is published twice a year, i.e. every August and February.Manila, Philippines: February 28, 2018.Prof. Dr. Jose M. Ocampo, Jr.A Guest Editor of EDUCARE Journal in Bandung, West Java, Indonesia; and a Full Professor at the Faculty of Education Sciences PNU (Philippine Normal University) in Manila, Philippines.Â